UTILIZING AUTHENTIC VIDEOS: AN ACTION RESEARCH TO ENHANCE STUDENTS' ABILITY IN DEVELOPING THEIR SPEAKING CONTENT - Yeskha Martika Megariani (Sanata Dharma University Yogyakarta, 2018)
Conducting a classroom action research, this study explores how the utilization of authentic videos can enhance students ability in developing the content of their speaking. A preliminary study which is done by the researcher shows that a group of 10th grade students had a problem in developing their speaking content in English class. Therefore, the researcher determined to use authentic videos in order to solve this problem and improve students ability in developing speaking content. These authentic videos are expected to attract students attention as well as give good and authentic models about delivering the message, speaking organization, idea development, and transitions. The findings, from students score, interview, and observation, and its analysis indicate that the use of authentic videos were effective enough in enhancing students speaking content development. Besides, students also learned how to pronounce certain expressions, use good intonation in telling something, manage their facial expression and body language when they speak with others, and so on.DOI:http://e-journal.usd.ac.id/index.php/IJIET/article/view/957/749